The handbook of Himalayan environments, development and wellbeing
1 online resource.
Keywords: "With contributions by over 70 leading scholars from across the social sciences, humanities and natural sciences, The Routledge International Handbook of Himalayan Environments, Development and Wellbeing explores the interrelationships that have emerged from environmental changes, development endeavors, and individual and community wellbeing. This handbook covers the entire Himalayas, from the Indian Himalayan region in the east to Bhutan, Nepal, Tibet (TAR), India, and the Gilgit-Baltistan region in the west. The shifting grounds of relationships between peoples, livelihoods, and territories affected by global warming require new ways of thinking, and new kinds of politics than the sovereignties of idealised European nation states. Divided into three distinctive sections (Environments, Developments and Wellbeings), this handbook brings together engaging accounts of the socio-cultural diversity and cross-fertilization so characteristic of the Himalayan region that have emerged from field research conducted in close interaction with communities and people experiencing and responding to climatic and socio-economic transformation. Across over 50 chapters, the handbook's contributors explore people's creative ways for understanding, adapting, and seeking wellbeing in environmental relations and development possibilities. This handbook will inform interested scholars, students, stakeholders and the public about the shifting grounds of relationships between Himalayan peoples, livelihoods, and territories affected by global warming and development politics and processes. Lessons about learning from Indigenous and local peoples, about governance of forests and water, and of grassroots conservation practices from the Himalayan region can help inform global networks of researchers and practitioners"--